Z dziejów rzymskich caligae = Of the history of Roman caligae - Budzanowska-Weglenda, Dominika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
For the military successes of the Roman army, the roads and armaments of soldiers were important. Characteristic for Roman legionnaires were their sandals, "caligae", cut from one piece of leather, tied with a strap. They had a thick, studded sole, made of three layers of leather. In winter, they were insulated with fabric or fur. About the appearance and meaning of "caligae" provide, among others Roman literature and sculptures. From "caligae" comes the nickname of Emperor Caligula.
Keywords: caliga; military footwear; Rome; obuwie wojskowe; Rzym